Factors Affecting Consumer Preferences and Demand for Ornamental Plants - Hayk Khachatryan (EDIS)
The primary goal of this study is to assist industry participants by providing information about consumer purchasing preferences, including information about past and future expenditures on ornamental plants, plant-specific, and store-specific factors that influence purchase decisions. Additionally, the study sought to determine whether providing consumers with information about the health and well-being, environmental, and economic benefits of ornamental plants had any effects on consumer preferences for ornamental plants. The main results of the survey are briefly summarized below. This 5-page fact sheet was written by Hayk Khachatryan and Hee Jung Choi, and published by the UF Department of Food and Resource Economics, February 2014.